Zufallsbefund Schilddrüsenknoten: Stellenwert der Sonographie und Szintigraphie in der Primärdiagnostik - Richter, Daniel; Beck, Michael; Müller, Sarina Katrin; Iro, Heinrich; Koch, Michael; Sievert, Matti (HNO, 2024)
Due to the widespread use of high-resolution sonography, numerous thyroid nodules are diagnosed, often as incidental findings. The challenge lies in evaluating various criteria such as size, shape, and echogenicity to assess the nodules’ malignancy risk. Risk stratification systems have been developed to enable systematic assessment as well as to avoid unnecessary medical interventions and malignant findings being overlooked. This article provides an overview of the current diagnostic standards in primary assessment of thyroid nodules.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Calcitonin; Cytology; Diagnostic imaging; Fine needle aspiration; Thyroid neoplasms